Harmonising careers: opera, hospitality and tourism industries unite to elevate graduate students employability - Sakhiseni Joseph Yende (Cogent Social Sciences)
This study delves into the transformative impact of integrating opera, hospitality and tourism education, signifying a paradigm shift in career development. Through participant feedback, it illuminates how this integration markedly advances graduates’ skill sets and career trajectories. Drawing on Social Exchange and Human Capital Theories, it showcases how this model enhances employability, bestowing graduates with a unique fusion of artistic flair and practical hospitality expertise. Employing a qualitative approach, the research gathers detailed responses from participants with integrated education. The study uncovers a notable enhancement in graduates’ communication, teamwork, adaptability and problem-solving proficiencies. Moreover, it highlights the refinement of attention to detail, leadership skills, creativity and cultural awareness, amplifying readiness for leadership roles and unconventional career paths. These findings hold significant implications for higher education, accentuating the importance of interdisciplinary integration in preparing graduates for contemporary industries. Furthermore, it underscores the interconnectedness of opera, hospitality and tourism, catalysing innovative educational approaches that bridge artistry with practicality. This study makes a distinctive contribution to discussions on graduate students’ employability, illustrating how integrating opera, hospitality and tourism education furnishes graduates with a sought-after skill set.